2016
DOI: 10.1371/journal.pone.0147221
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Annotation of the Parastagonospora nodorum Reference Genome Using Next-Generation Genomics, Transcriptomics and Proteogenomics

Abstract: Parastagonospora nodorum, the causal agent of Septoria nodorum blotch (SNB), is an economically important pathogen of wheat (Triticum spp.), and a model for the study of necrotrophic pathology and genome evolution. The reference P. nodorum strain SN15 was the first Dothideomycete with a published genome sequence, and has been used as the basis for comparison within and between species. Here we present an updated reference genome assembly with corrections of SNP and indel errors in the underlying genome assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 65 publications
(99 reference statements)
1
52
0
1
Order By: Relevance
“…Previous studies on Con7 have reported the gene to have different splicing variants (Odenbach et al ., ; Ruiz‐Roldán et al ., ). By analysing previously published RNA‐seq data from P. nodorum (Syme et al ., ), four alternative splicing variants of PnCon7 were identified. The 1553bp PnCon7 pre‐mRNA was processed to 4 variants, which differ only at the boxed 5′ regions (alternative splicing region) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on Con7 have reported the gene to have different splicing variants (Odenbach et al ., ; Ruiz‐Roldán et al ., ). By analysing previously published RNA‐seq data from P. nodorum (Syme et al ., ), four alternative splicing variants of PnCon7 were identified. The 1553bp PnCon7 pre‐mRNA was processed to 4 variants, which differ only at the boxed 5′ regions (alternative splicing region) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of previously published RNAseq data revealed four alternative splicing variants of PnCon7 (Syme et al ., ). These analyses were subsequently verified through experimental approaches as described above.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, broad host‐range necrotrophic fungal pathogens such as S. sclerotiorum and B. cinerea exhibit relatively repeat‐poor genomes (Derbyshire et al , ; Van Kan et al , ). Nevertheless, effector genes may also be associated with repeat sequences in necrotrophic fungi and fungi with a broad host range (Dallery et al , ; Laurent et al , ; Syme et al , ; Wang et al , ). Secretome analyses highlighted a number of candidate effector‐like proteins in the genome of S. sclerotiorum (Badet et al , ; Derbyshire et al , ; Guyon et al , ; Heard et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the homology on the ToxA ‐containing scaffolds alone, an initial Mauve alignment was conducted with the full‐length scaffold from P. tritici‐repentis (http://fungi.ensembl.org/Pyrenophora_triticirepentis/Info/Index) and P. nodorum (http://fungi.ensembl.org/Pyrenophora_triticirepentis/Info/Index) (Manning et al ., ; Syme et al ., ) and the de novo scaffold from B. sorokiniana . The Mauve alignment was conducted with the setting to automatically calculate the seed weight and the minimum Locally Collinear Block (LCB) score.…”
Section: Methodsmentioning
confidence: 99%